The Influences of Foreign Direct Investments, the Economic Advantages Offering in Macedonian Economy - Dumi, Alba; Memeti, Florina; Qazimi, Jeton (Mediterranean Journal of Social Sciences, 2012)
In this paper we want to illustrate the facts that both means of supplying markets exporting and production in those markets.Moreover, there are two international business activities that we are studying in our paper research. Among, the companies Forbes(2000) listed as the 100 largest U.S multinationals companies. According the World Investment Report small and middle enterprisesaccount for 20.8% of the total 3.470 U.S. In this paper we analyze two topics directly related to exporting and production in foreigncountries to compare with foreign investments in Republic of Macedonia. The aim of this study is to analyze: (1) international trade whichincludes exports and imports in Republic of Macedonia, (2) foreign direct investments which international polices in Republic ofMacedonia must make to establish and expand the activity components and products in Republic of Macedonia. Todayâ€™s multinationalscreate widespread network of research, component production assembly and distribution.â€ We want together date from the developmentof foreign investments of Republic of Macedonia. There are a number of advantages of in focusing attention on a national that is alreadysizable purchaser of goods coming from would â€“ be exporter country.